2019
DOI: 10.1097/nmd.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Negative Experiences in Childhood, Parental Style, and Resilience Among People Reporting Paranormal Experiences

Abstract: There are relatively few studies examining the parental style, childhood trauma, and paranormal experiences/beliefs; therefore, the aim of this study is to measure the dominant parental style of those who have experienced paranormal events and their correlation with negative events in childhood and resilience. Four questionnaires were administered to 644 participants. The results showed high frequency of experiences such as sense of presence, premonitory dreams, telepathy, mystical experiences, apparitions, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Several studies reported findings that were partially inconsistent with their hypotheses or past research (Barahmand & Heydari Sheikh Ahmad, 2016;Dolphin et al, 2015;Marulanda & Addington, 2016;Mętel et al, 2020;Nitzburg et al, 2016;Rossi et al, 2021;Ruzibiza et al, 2018). Additionally, several studies also reported findings that were contrary to their hypotheses or past research (Mętel et al, 2020;Parra, 2019;Ruzibiza et al, 2018). A careful review of these inconsistent and contrary findings (e.g., how certain aspects of resilience may not be protective or may exacerbate mental health outcomes) can highlight important limitations of past work as well as considerations for future resilience work in this area.…”
Section: Main Resilience Findingsmentioning
confidence: 95%
See 1 more Smart Citation
“…Several studies reported findings that were partially inconsistent with their hypotheses or past research (Barahmand & Heydari Sheikh Ahmad, 2016;Dolphin et al, 2015;Marulanda & Addington, 2016;Mętel et al, 2020;Nitzburg et al, 2016;Rossi et al, 2021;Ruzibiza et al, 2018). Additionally, several studies also reported findings that were contrary to their hypotheses or past research (Mętel et al, 2020;Parra, 2019;Ruzibiza et al, 2018). A careful review of these inconsistent and contrary findings (e.g., how certain aspects of resilience may not be protective or may exacerbate mental health outcomes) can highlight important limitations of past work as well as considerations for future resilience work in this area.…”
Section: Main Resilience Findingsmentioning
confidence: 95%
“…These measures ranged from questions about specific events, such as a regional earthquake (Rossi et al, 2020), to multiple questions about various potential traumas, such as racism, bullying, and bereavement (Dolphin et al, 2015). Six studies focused specifically on childhood abuse (Marulanda & Addington, 2016;Mętel et al, 2020;Mongan et al, 2019;Parra, 2019;Rossi et al, 2019Rossi et al, , 2021.…”
Section: Trauma or Stressful Experiences Measurementmentioning
confidence: 99%
“…The hypotheses are presented together with a brief statement for each hypothesis regarding the degree of support received from the empirical evidence. 3 H1: SPEs should be more common in people reporting CA -supported by 12 out of 12 studies: French and Kerman (1996), Irwin (1992Irwin ( , 1994, Lawrence et al (1995), Parra (2019), Perkins and Allen (2006), Rabeyron and Watt (2010), Rogers and Lowrie (2016), C. A. Ross and Joshi (1992), Sar et al (2014), Scimeca et al (2015), and Wright (1999).…”
Section: Hypothesesmentioning
confidence: 99%
“…H1: SPEs should be more common in people reporting childhood abuseconfirmed: [112,[176][177][178][179].…”
Section: Hypothesesmentioning
confidence: 99%